Biochar: aplicaciones y efectos en combinación con fertilizantes minerales en 3 variedades de café en la provincia de El Oro - Quiñonez Leon, Bryan Samuel (Machala : Universidad Técnica de Machala, 2020)
Coffee growing is traditional in Ecuador, it can be produced in two types, Arabica coffee and Robusta coffee, since our country has privileged agroecological aptitudes for the development of both species. The cultivation of coffee is very important, it can be cultivated in a wide diversity of soils, being more important to have it in an agroforestry system so that resources are conserved, carbon is captured and the water balance is protected. Coffee is grown in 23 provinces of Ecuador, it is considered that Coffea arabica arrived in our country in 1784 and that Coffea canephora was introduced in 1951, starting its production at the Pichilingue Experimental Station and then distributed to the rest of the country. At present, coffee cultivation has decreased because it is no longer profitable, pests attacked and decimated the crops, so it is not beneficial and its maintenance became an enormous cost, coffee growers changed crops replacing it with grasslands, cocoa farms, plantations forest and fruit trees, according to the II Agricultural Census, coffee went from being cultivated in about 346,971 hectares to being cultivated in just 60,000 hectares, according to data released by ANECAFÉ in 2019. In this experimental work, the application of biochar and complete fertilizer will be carried out to evaluate three commercial varieties of coffee that are produced in the province of El Oro, which are: Sarchimor, Conilón and Lojana. Biochar has become a relevant research material due to its varied application and great benefits granted to crops such as stimulating microbial symbiosis and making the application of fertilizers more efficient, improving the production and yield of crops and increasing biomass, It favors the production of phytoalexins so that the plant defends itself against pathogenic organisms, improving its resistance. Coffee tree nutrition demands 16 or more elements that are essential for its metabolism and that vary according to the needs of the species, phenological stage or depends on the properties of the soil where it will be planted. The experimental design was randomized blocks with 12 treatments and four repetitions each, with doses of zero, five, ten and fifteen grams of biochar, mixed with 20 g of complete fertilizer except for the control, the variables analyzed were: height of the plant (AP), number of branches (NR), root length (LR), root perimeter (AR), leaf length (LH), leaf width (AH). The results obtained indicate that the best doses were 5 and 15 g of biochar, which achieved excellent results with the Sarchimor variety, while the Lojana and Conilon varieties obtained lower values, possibly affected by their genetics. The AP variable indicates that the Sarchimor variety obtained a higher plant height in the assigned treatments, the ST3BY15 and ST1BY5 treatments have a height of 75 cm, while the lowest heights among the three varieties analyzed are all those at which no made application of biochar LTBY0, ST0BY0 and CT0BY0. The LR variable is significant, their means indicate that the ST3BY15 and LT3BY15 treatments show greater root elongation with 53 and 43 cm respectively, the addition of biochar activated the mycorrhizae and these stimulated the development of the root system with a better uptake of phosphorus found associated with increasing the growth rate of the roots. It is concluded that the best doses in all treatments are 5 and 15 g of biochar for best results and that the variety with the best response to these treatments was Sarchimor. It is recommended to use biochar in a mixture with fertilizers to enhance its effect on plants, prevent their loss, improve CEC, among other benefits that improve coffee cultivation.
La caficultura es tradicional en Ecuador, se puede producir de dos tipos, café arábigo y café robusta ya que nuestro país goza de privilegiadas aptitudes agroecológicas para el desarrollo de ambas especies. El cultivo de café es muy importante, se puede cultivar en una amplia diversidad de suelos, siendo más importante tenerlo en un sistema agroforestal de manera que se conserven los recursos, se capture carbono y se proteja el balance hídrico. El café se cultiva en 23 provincias del Ecuador, se considera que Coffea arabica llegó a nuestro país en 1784 y que Coffea canephora fue introducida en 1951 iniciando su producción en la Estación Experimental Pichilingue y luego se distribuyó al resto del país. En la actualidad el cultivo de café ha disminuido porque dejó de ser rentable, las plagas atacaron y diezmaron los cultivos por lo que no resulta beneficioso y se convirtió en un enorme costo su mantenimiento, los caficultores cambiaron de cultivo sustituyéndolo por pastizales, cacaoteras, plantaciones forestales y frutales, según el II Censo Agropecuario el café pasó de ser cultivado en cerca de 346 971 has a ser cultivado en apenas 60 000 has según datos difundidos por ANECAFÉ en 2019. En este trabajo experimental se realizará la aplicación de biochar y fertilizante completo para evaluar tres variedades comerciales de café que se producen en la provincia de El Oro que son: Sarchimor, Conilón y Lojana. El biochar se ha convertido en un material de investigación relevante por su variada aplicación y grandes beneficios otorgados a los cultivos como estimular la simbiosis microbiana y hacer más eficiente la aplicación de fertilizantes, mejora la producción y rendimiento de los cultivos e incremento de la biomasa, favorece la producción de fitoalexinas para que la planta se defienda de organismos patógenos mejorando su resistencia. La nutrición del cafeto demanda 16 o más elementos que son esenciales para su metabolismo y que varía de acuerdo a las necesidades de la especie, etapa fenológica o depende de las propiedades del suelo donde será sembrado. El diseño experimental fue de bloques al azar con 12 tratamientos y cuatro repeticiones cada uno, con dosis de cero, cinco, diez y quince gramos de biochar, mezclados con 20 g de fertilizante completo a excepción del testigo, las variables analizadas fueron: altura de la planta (AP), número de ramas (NR), largo de raíz (LR), perímetro de raíz (AR), largo de las hojas (LH), ancho de las hojas (AH). Los resultados obtenidos indican que las mejores dosis fueron de 5 y 15 g de biochar que lograron excelentes resultados con la variedad Sarchimor, mientras que las variedades Lojana y Conilon obtuvieron menores valores posiblemente afectados por su genética. La variable AP indica que la variedad Sarchimor obtuvo una mayor altura de plantas en los tratamientos asignados, los tratamientos ST3BY15 y ST1BY5 presentan una altura de 75 cm, mientras que las alturas más bajas entre las tres variedades analizadas son todas aquellas a las que no se realizó aplicación de biochar LTBY0, ST0BY0 y CT0BY0. La variable LR es significante, sus medias indican que los tratamientos ST3BY15 y LT3BY15 presentan mayor elongación radicular con 53 y 43 cm respectivamente, la adición de biochar activó las micorrizas y estas estimularon el desarrollo del sistema radicular con una mejor captación de fósforo que se encuentra asociado con el incremento de la tasa de crecimiento de las raíces. Se concluye que las mejores dosis en todos los tratamientos son 5 y 15 g de biochar para mejores resultados y que la variedad con mejor respuesta a estos tratamientos fue Sarchimor. Se recomienda usar biochar en mezcla con fertilizantes para potenciar su efecto en las plantas, evitar su pérdida, mejorar la CIC entre otros beneficios que mejoraran el cultivo de café.
Keywords: PRODUCCIÓN; RENDIMIENTO; FITOSANIDAD; NUTRICIÓN